Historical dictionary of children's literature - O'Sullivan, Emer, 1957- (Historical dictionaries of literature and the arts ;, 2010)
Children's literature comes from a number of different sources-folklore (folk- and fairy tales), books originally for adults and subsequently adapted for children, and material authored specifically for them-and its audience ranges from infants through middle graders to young adults (readers from about 12 to 18 years old). Its forms include picturebooks, pop-up books, anthologies, novels, merchandising tie-ins, novelizations, and multimedia texts, and its genres include adventure stories, drama, science fiction, poetry, and information books. The Historical Dictionary of Children's Literatur.